Evaluation of Coiling Effects on the Return Loss of Twisted Copper Communication Cables - Olusegun Ogundapo (Theory and Applications of Engineering Research Vol. 6, 2024)
Twisted copper cables (TCCs) is a crucial part of the framework for Internet of Things (IOT). In Ethernet cabling communication systems, return loss is a major signal limiting factor that needs to be evaluated before deployment. The prevalence of sub-standard and copper clad aluminum (CCA) cables in the market makes a method of evaluating cables necessary to minimize signal degradation after installation. Installation stresses are also anticipated from repeated coiling and uncoiling of cables. There is the need for an objective method of evaluating TCCs selected for deployment. In this paper, four category 6 unshielded TCCs from different manufacturers including one CCA cable were selected for the test. In this paper, the four cables were subjected to repeated coiling tests anticipated during installation to obtain their return loss. The Feature Selective Validation (FSV) tool which is a standardized tool for objectively comparing data sets was used to evaluate their resilience or otherwise to the effects of the coiling. The results show that the CCA cable gave the highest variations in return loss from the coiling tests in all the four pairs. This indicates that the CCA cable presented the least resilience to the cables manipulation and has the highest potential to degrade after installation. The method provided can be used by cable installers and engineers to undertake an objective evaluation of TCCs performance measurements before deployment. This can help them minimize potential liabilities that may arise from installing substandard cables such as fire outbreak and poor quality of service.